Land-use trends related to Natura2000 sites in Denmark. (July 2018) - Levin, Gregor; Frederiksen, Pia; Nainggolan, Doan
Abstract: EU-member states are obliged to designate Natura2000 sites for habitat protection. Natura2000 sites comprise approximately 18% of the terrestrial area of the EU. On average, around 22% of Natura2000 sites are covered by agricultural land use, such as intensive cropland and more extensively managed land. Particularly in regions with high proportions of agricultural land use in Natura2000 sites, habitat protection is closely linked with the intensity of agricultural land use. Thus, it is important to understand dynamics between intensive and extensive land use. Denmark, where Natura2000 sites comprise approximately 8% of the terrestrial area, is the EU member state with the highest proportion of agricultural land use in Natura2000 sites. The Habitat Directive (HD) was implemented in Denmark in 2003. This implied increased focus from authorities on extensification of agricultural land use in Natura2000 sites. We applied data from agricultural registers to test if the implementation of the HD had a significant effect on extensification of agricultural land use within Natura2000 sites compared to areas outside Natura2000. We assessed area of extensive land use in 2013 and change in area of extensive land use for two periods: From 2000–2003, before the implementation of the HD and from 2003 to 2013, after its implementation. In order to control for the influences of biophysical constraints on agricultural intensity, we included information on slopes and peat soil. Results: from a regression analysis indicate that even if influences of peat soils and slopes are taken into account, Natura2000 sites are positively related to the extent of extensive land use in 2013 and to the magnitude of extensification. Furthermore, this relation is more significant in the period after 2003, indicating that the implementation of the HD had an extensifying effect on agricultural land use within Nautra2000 sites.